An Assessment of Urban Tourists’ Perceptions of the Objective Aesthetics of High-Rise Residential Towers’ Facades (Case Study: Tehran’s Region 22) - Sepehr Farhadi Matin; Ali Mashhadi (گردشگری و اوقات فراغت, 2024)
Nowadays, many aesthetic concepts in the field of towers have been imposed on tourists through fashion, such as Roman, neoclassical, and... Instead of conveying meaning, these buildings have only become a means of consumption and repetition of fashion in the society. This reproduction of fashion without paying attention to the principles of European classical and neoclassical architecture and only taking its external elements such as columns, statues, etc., not according to the standards of this architecture, but sometimes accompanied by its change, and only the image of fashion architecture It has been shown. In addition, there is no provision for measuring the taste of urban tourists in this field. The purpose of writing this article is to compare the factors that play a role in tourists' perception of the objective aesthetics of high-rise residential towers. The type of research in this research is practical. The research method in this research is qualitative and based on descriptive, analytical and comparative approach. In order to collect data from semi-structured interviews and in the process of data analysis, Atlas software was used. The results of this realization consist of three parts. In the first part, there are components that have been mentioned by more people and also have more commonality among the towers, among which, as the component with the highest commonality and influence, the "component" A high variety of shapes can be seen. The second part of the conclusion is also related to the correlation of objective aesthetic components in the facade of the towers.